PERSPEKTIF KESETARAAN DAN KEADILAN GENDER HUSEIN MUHAMMAD DALAM SILANG PENDAPAT KHITAN PEREMPUAN - Hikmalisa; Dona Kahfi Ma Iballa (Institut Agama Islam Syubbanul Wathon Magelang, 2022)
This article discusses circumcision from a feminist Kiai perspective, Husein Muhammad. This research is a qualitative descriptive study with a literature study style and uses a gender approach. The results of this study indicate that Husein Muhammad interprets the law of female circumcision by prioritizing the principles of justice and gender equality. For him, circumcision is purely result of construction by some classical Muslim scholars because there is nothing in the Qur'an or Hadith that can be used as argumentation that indicates its obligation of circumcision for women. In addition, female circumcision for him is damaging to health means this practice is also forbidden in Islam.